Michel Foucault, The Class of January 6, 1982 - Kiosoglou, Thanos (Conatus - Journal of Philosophy, 2017)
Greek translation of M. Foucault, L'Hermeneutique du sujet: Cours au Collège de France (1981-1982) (Paris: Gallimard, 2001).